2021
DOI: 10.21037/apm-21-1280
|View full text |Cite
|
Sign up to set email alerts
|

The effect of balloon dilatation eustachian tuboplasty combined with grommet insertion on the structure and function of the eustachian tube in patients with refractory otitis media with effusion

Abstract: Background: The treatments for refractory secretory otitis media with effusion usually choose long-term grommet insertion. This study evaluated the effect of balloon eustachian tuboplasty combined with grommet insertion on the function and the opening length of the eustachian tube in patients with refractory otitis media with effusion.Methods: Fifty-seven patients with refractory otitis media with effusion were enrolled. A threedimensional reconstruction of an iohexol-enhanced computed tomography image was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…e new type of quinolone broad-spectrum antibacterial drugs can reduce the drug tolerance of bacteria, greatly improve the bactericidal activity of drugs, and effectively curb the generation of drug resistance. It acts on bacterial type II-A topoisomerases (DNA rotase and topoisomerase IV) [2][3][4]. Studies have shown that the process of bacterial DNA replication is essential for the growth and survival of bacteria, and this process requires the combined action of DNA rotase and topoisomerase IV [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e new type of quinolone broad-spectrum antibacterial drugs can reduce the drug tolerance of bacteria, greatly improve the bactericidal activity of drugs, and effectively curb the generation of drug resistance. It acts on bacterial type II-A topoisomerases (DNA rotase and topoisomerase IV) [2][3][4]. Studies have shown that the process of bacterial DNA replication is essential for the growth and survival of bacteria, and this process requires the combined action of DNA rotase and topoisomerase IV [4].…”
Section: Discussionmentioning
confidence: 99%
“…It acts on bacterial type II-A topoisomerases (DNA rotase and topoisomerase IV) [2][3][4]. Studies have shown that the process of bacterial DNA replication is essential for the growth and survival of bacteria, and this process requires the combined action of DNA rotase and topoisomerase IV [4]. e treatment of new quinolones with broad-spectrum antibacterial drugs forms a "drug-topoisomerase-DNA" triple complex interaction and promotes the molecular processing law of the complex to release broken DNA, thereby deepening the understanding of the bactericidal mechanism of quinolones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BET as a minimally invasive intervention first described in 2010 has been successfully investigated by randomized control trials and clinical studies in the past decade [ 29 , 30 ]. Considering BET surgery did not achieve significant symptom improvement of OM, the combination treatment with BET and Grommet insertion has been evaluated in OM [ 12 , 31 , 32 ] and ETD [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has generally been considered that surgery for improving hearing can be considered only when eustachian tube function becomes normal [ 36 ]. COME patients treated with BET and grommet insertion was reported to have an improvement in eustachian tube function and structure [ 12 , 32 ]. In a previous study, the ETDQ-7 score with total score of ≥14.5 (mean score of ≥2.1) showed 100% sensitivity and 100% specificity for categorizing a patient as having ETD [ 37 ].…”
Section: Discussionmentioning
confidence: 99%